Pengaruh Kualitas Produk, Persepsi Harga dan Cita Rasa Terhadap Kepuasan Konsumen di Rumah Makan Pak Abbas Dikalangan Masyarakat Kota Pekanbaru - Rohima Nugra Heni; Ulfiah Novita (Yayasan Almanar Pujud, 2025)
Customer satisfaction is a key factor in determining the quality of a business, particularly in the culinary industry. Rumah Makan Pak Abbas is one of the well-known restaurants among the people of Pekanbaru City. It is famous for its traditional Malay dishes, such as asam pode baung sungai (a sour river catfish dish), fried free-range chicken, and cincang daging (minced meat stew). The purpose of this study is to determine the influence of product quality, price perception, and taste on customer satisfaction at Rumah Makan Pak Abbas. This research uses a quantitative approach with the multiple linear regression method. The research sample consisted of 95 respondents, selected using the purposive sampling technique. Data was collected through the distribution of questionnaires to customers. The results of this study indicate that product quality, price perception, and taste each have a significant partial effect on customer satisfaction at Rumah Makan Pak Abbas.